INVESTIGATING THE COLLOCATION OF THE WORDS 'MOM' AND 'DAD' IN ALEC GREVEN'S NOVELS: A CORPUS LINGUISTIC ANALYSIS OF SEMANTIC PREFERENCES AND PROSODY - Zuraida, Ida; Simatupang, Ervina CM (English Review: Journal of English Education, 2023)
This research delves into the collocation and semantic analysis of the words "Mom" and "Dad" in two novels, "How to Talk to Mom?" and "How to Talk to Dad?", authored by a teenage male writer, Alec Greven. The primary objective is to investigate the frequency of occurrence of these parental terms and explore their semantic preferences and prosody within the context of dictions used in the novels. The study uses a mixed-method design, incorporating both quantitative and qualitative approaches to achieve a comprehensive understanding of the research topic. Using corpus linguistic methods, the study examines the frequency of the words "Mom" and "Dad" in each novel, revealing that "Mom" occurs more frequently than "Dad." Through concordance hits, the collocational patterns of the parental terms are analyzed, shedding light on the contexts in which they are commonly used. The collocation analysis demonstrates that "Dad" is frequently associated with family, friendship, and engaging activities, while "Mom" is linked to family, household chores, and maternal preferences. Furthermore, the research explores the semantic prosody of "Mom" and "Dad" revealing that "Dad" is portrayed more positively compared to "Mom."